Prolactin and zinc in dialysis patients - Castro, AVB; Caramori, J.; Barretti, Pasqual [UNESP]; Baptistelli, E. E.; Brandao, A.; Barim, E. M.; Padovani, Carlos Roberto [UNESP]; Aragon, F. F.; Brandao-Neto, J. (Humana Press Inc, 2002)
The objectives of the present study were to investigate the frequencies of hyperprolactinemia and hypozincemia in patients undergoing hemodialysis (HD) or continuous ambulatory peritoneal dialysis (CAPD), the associations between blood levels of zinc (Zn2+) and hormones, and dietary zinc intake amount and its relation to zincemia. We studied 28 patients (14 HD and 14 CAPD) who had their blood levels of Zn2+, prolactin (PRL), parathyroid hormone (PTH), and gonadotropins (LH, FSH) evaluated. Thirteen patients had dietary nutrient amounts evaluated from a 3-d nutritional record. Hyperprolactinemia occurred in 29% patients (HD = CAPD), hypozincemia in 62% (20% HD and 42% CAPD), and low dietary Zn2+ intake in 90% of patients. No correlation among blood concentration of Zn2+ and PRL, PTH, LH, and FSH were observed in the two modalities of dialysis or between zincemia and Zn2+ ingestion. We concluded that the occurrence of hyperprolactinemia and hypozincemia were not related to dialysis modality and that zincemia did not reflect the observed low dietary intake of Zn2+.
Keywords: peritoneal dialysis; hemodialysis; prolactin; parathyroid hormone; luteinizing hormone; follicule-stimulating hormone; zinc